Answer:
Answer is 5
Step-by-step explanation:
Okay hun so let me tell u what's up here
They give us this equation and ask for the 'roots'
(x+5)^3(x-9)(x+1)
Now lemme tell you the roots of this one
-5, 9, -1
you get this from making each of them 0
The answer to this would be "3" because there are 3 roots, buT wait theRe'S mOre
(x+5) goes 3 times
So thy must recount it
-5, -5, -5, 9, -1 <-- These are the roots
that's 5 roots in total
....also I did this on edgen, got it right with 5
Answer: 18x2 + 69x + 65
Step-by-step explanation:
(3x + 5) (~6x + 13)
1. 3x(6x + 13) + 5(6x + 13)
2. 18x2 + 39x + 5(6x + 13)
3. 18x2 + 39x + 30 + 65
4. 18x2 + 69 + 65
Answer:
x=0,y=-3
Step-by-step explanation:
3x-5y=15 - equation(1)
x-4y=12 => x=12+4y -equation (2)
Replace equation (2) in equation (1)
3(12+4y)-5y=15
36+12y-5y=15
7y=15-36
7y= -21
y = -21/7
y=-3
If y=-3,then replace in equation (1) ; 3x -5(-3)=15
3x+15=15
3x=0
x=0
You can write this ratio in two other ways:
7 to 13
7 : 13